Asthma prevalence and control levels among Special Olympics athletes, and asthma‐related knowledge of their coaches. Issue 4 (19th December 2018) - O'Neill, C.; Russell, M.; Balogh, R.; Lloyd, M.; Dogra, S.
Abstract: Background: The prevalence of asthma among athletes with intellectual disabilities, and the asthma knowledge levels of their coaches, is unknown. Methods: Special Olympics Canada athletes completed a demographic questionnaire ( n  = 208). Athletes who identified as having ever or current asthma completed the Asthma Control Questionnaire and the Mini Asthma Quality of Life Questionnaire and were measured for height, weight and lung function ( n  = 73). National level coaches ( n  = 27) completed a questionnaire pertaining to asthma knowledge. Results: The prevalence of ever and current asthma were 35.5% ( n  = 73) and 21.1% ( n  = 44), respectively. Athletes with asthma reported that they had inadequately controlled asthma, but good quality of life. Coaches correctly answered 43% true/false questions on the survey, indicating suboptimal asthma knowledge. Conclusions: Athletes with intellectual disabilities appear to have a greater prevalence of asthma than the general population; however, coaches of these athletes appear to have limited knowledge pertaining to asthma and exercise‐induced asthma.